2002
DOI: 10.1258/00222150260369462
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative radiation therapy for advanced-stage oropharyngeal cancer

Abstract: Between 1985 and 1999, 43 patients with locally-advanced, resectable oropharyngeal cancer were treated with combined surgery and post-operative radiation therapy (RT) at Oregon Health and Science University. Five patients (12 per cent) had Stage III disease and 38 patients (88 per cent) had Stage IV disease. All patients had gross total resections of the primary tumour. Thirty-seven patients had neck dissections for regional disease. RT consisted of a mean tumour-bed dose of 63.0 Gy delivered in 1.8-2.0 Gy fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Surgery and postoperative irradiation for advanced stage (stages III and IV) carcinoma of the oropharynx is an accepted treatment modality that can provide excellent local and locoregional control. In a recent study from our institution, Hansen et al 2 demonstrated that this combined treatment yielded, at 5 years, a 96% local control and 80% locoregional control, comparable with previously reported results. 3 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Surgery and postoperative irradiation for advanced stage (stages III and IV) carcinoma of the oropharynx is an accepted treatment modality that can provide excellent local and locoregional control. In a recent study from our institution, Hansen et al 2 demonstrated that this combined treatment yielded, at 5 years, a 96% local control and 80% locoregional control, comparable with previously reported results. 3 …”
Section: Discussionsupporting
confidence: 88%
“…Surgery and postoperative irradiation combined is a commonly used treatment approach, with good local and regional control and acceptable long‐term survival. 2,3 Organ‐preservation protocols, including various combinations of chemotherapy and radiation therapy, have more recently been introduced in attempts to address the risk of distant metastases, as well as locoregional disease, and also to potentially reduce functional and cosmetic morbidities thought to be associated with surgery. 4 However, functional outcome after surgical treatment for advanced oropharyngeal carcinoma is not uniformly agreed on, and there is no clear consensus on typical postoperative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, palate SCC appear to have increased local aggressively, easily invading adjacent muscle and bone structures and thereby leaving behind important morpho-functional defects [ 14 ]. In addition, the tumors developed at the level of the soft palate seem to be much more aggressive, the five-year overall survival rate dropping from 91% for the T1 tumors [ 15 ] to 33% in the case of T4 tumors [ 16 ]. Considering these particularities, in the present study, we investigated the IHC expression of the D2-40, Gal-3, Maspin and MCM7 immunomarkers, knowing that they play a major role in promoting loco-regional cancer invasiveness.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…The soft palate SCCs are aggressive tumors, with rapid onset and a major negative impact regardless of tumor size at diagnosis [ 26 ]. For the T1 and T2 soft palate SCCs was reported a five-year overall survival rate about 91% to 100% and respectively 70% to 75% [ 27 ], while for the T3 and T4 lesions despite multimodal treatment the rate values dropped to 33% to 47% [ 28 , 29 ]. The incidence of LN metastases for soft palate SCCs was estimated to be around 20% for T1–T2 tumors and about 60% to 70% for T3–T4 tumors [ 30 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%